2022
DOI: 10.1007/s12016-021-08912-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Antibody Immunity Against SARS-CoV-2: Comprehensive Review on Immunoassay and Immunotherapy

Abstract: The current COVID-19 global pandemic poses immense challenges to global health, largely due to the difficulty to detect infection in the early stages of the disease, as well as the current lack of effective antiviral therapy. Research and understanding of the human immune system can provide important theoretical and technical support for the clinical diagnosis and treatment of COVID-19, the clinical implementations of which include immunoassays and immunotherapy, which play a crucial role in the fight against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Antibody-based therapies has proven its e ciency against SARS-CoV-2 virus and appears to be the most promising approach to control COVID-19 pandemic. A number of neutralizing monoclonal antibodies used in clinical setting showed very good results particularly in stopping the disease progression [26,27]. However, constant emergence of new virus' variants hinder the potency of available anti-SARS-CoV-2 antibodies and urged the continuous development of improved more effective neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-based therapies has proven its e ciency against SARS-CoV-2 virus and appears to be the most promising approach to control COVID-19 pandemic. A number of neutralizing monoclonal antibodies used in clinical setting showed very good results particularly in stopping the disease progression [26,27]. However, constant emergence of new virus' variants hinder the potency of available anti-SARS-CoV-2 antibodies and urged the continuous development of improved more effective neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a positive association between antibody titres and disease severity and the probability of the risk of death in patients hospitalised with COVID-19. The authors of these studies have proposed that more severe disease stimulates more intensive antibody production [ 8 , 9 , 10 , 11 ]. This association was also apparent while measuring neutralising activity [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main difference between the studies that have connected higher titres of anti-SARS-CoV-2 antibodies with severe and fatal disease [ 8 , 9 , 10 , 11 ] and later studies that identified the protective role of the early development of strong antibody response [ 5 , 6 , 7 ] is the temporal factor. The studies that identified the early antibody response as a protective factor assessed it at the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially promising, the use of COVID-19 convalescent plasma (CCP) has not been effective in preventing disease progression for the majority of patients, as observed in the studies published to date [3] , [4] . Some factors that may explain the finding of discrepant and often frustrating results between studies may be the fact that, in most protocols, patients receive CCP from only 1 or 2 donors, in addition to the differences in antibody titers and their quantification methods, and different infusion times between the study protocols [5] .…”
Section: Introductionmentioning
confidence: 99%